Fabrication of uniform microlasers using conventional printing technology - Ta, Duong; Hoang, Thuong; Nguyen, Duy; Nguyen, Hoang; Nguyen, Toan (Communications in Physics, 2024)
In recent years, soft material microlasers have attracted great interest for their simple fabrication and potential in flexible photonic devices. Particularly, ink-jet printing technology offers an efficient method for the production of uniform microlasers. However, the ink-jet system is generally complex and expensive. In this work, we have successfully used a cost-effective standard printer for microlaser creation. By employing dye-doped glycerin-water for the printing ink, we can fabricate uniform dome shaped structures, the so-called hemispheres, with diameters from 35 to 70 µm on a hydrophobic coated dielectric mirror. Under optical pulse pumping at 532 nm, these hemispheres exhibit lasing emission with clear modes. The lasing mechanism is studied and ascribed to whispering gallery mode. Due to low optical loss, we achieve a lasing threshold of 32 µJ/mm² and a quality factor of 2100. Our method can be applied to diverse soft matter microlasers and the fabricated microlasers are promising for sensing applications.